Frontmatter [Front Cover, Editorial Team, Indexing, and Table of Contents] - L.M.F. Purwanto (JoDA Journal of Digital Architecture, 2022)
Frontmatter [Front Cover, Editorial Team, Indexing, and Table of Contents]